Mid-infrared trace-gas sensing with a quasi- continuous-wave Peltier-cooled distributed feedback quantum cascade laser - Weidmann, D.; Tittel, F. K.; Aellen, Thierry; Beck, Mattias; Hofstetter, Daniel; Faist, Jérôme; Blaser, Stéphane (My University, 2004)
A recently developed distributed feedback quantum cascade laser (QCL) capable of thermoelectric-cooled (TEC) continuous-wave (cw) operation and emitting at ~9 μm is used to perform laser chemical sensing by tunable infrared spectroscopy. A quasi-continuous-wave mode of operation relying on long current pulses (~5 Hz, ~50% duty cycle) is utilized rather than pure cw operation in order to extend the continuous frequency tuning range of the quantum cascade laser. Sulfur dioxide and ammonia were selected as convenient target molecules to evaluate the performance of the cw TEC QCL based sensor. Direct absorption spectroscopy and wavelength-modulation spectroscopy were performed to demonstrate chemical sensing applications with this novel type of quantum cascade laser. For ammonia detection, a 18-ppm noise-equivalent sensitivity (1 σ) was achieved for a 1-m absorption path length and a 25-ms data-acquisition time using direct absorption spectroscopy. The use of second-harmonic-detection wavelength-modulation spectroscopy instead of direct absorption increased the sensitivity by a factor of three, achieving a normalized noise-equivalent sensitivity of 82 ppbHz-1/2 for a 1-m absorption path length, which corresponds to 2×10-7 cm-1Hz-1/2.